[PP.26.03] ANTIHYPERTENSIVE EFFICACY OF INDAPAMIDE SR/AMLODIPINE IN HYPERTENSIVE PATIENTS AGED 65 YEARS AND ABOVE: A SUBANALYSIS OF THE 1-YEAR NESTOR STUDY. (September 2016) - Hanon, O.
Abstract : Objective: The SPRINT study recently demonstrated that lowering systolic blood pressure is particularly beneficial in reducing cardiovascular outcomes in older patients, with guidelines recommending diuretics and calcium channel blockers (CCBs) to treat systolic hypertension in this age group. The objective of this subanalysis of the NESTOR study was to evaluate the long-term antihypertensive efficacy and safety of indapamide SR/amlodipine in patients aged 65 years and above, over a period of 1 year. Design and method: The NESTOR study included 570 hypertensive (aged 35–80 years, systolic blood pressure [SBP] 140–180 and diastolic blood pressure [DBP] <110 mmHg), diabetic patients with microalbuminuria, 187 of whom were aged 65 years and above. Antihypertensive therapy was stopped before inclusion and indapamide SR 1.5 mg or enalapril 10 mg administered. If target BP (<140/90 mmHg) was not achieved at 6 weeks, amlodipine 5 mg was added with uptitration to 10 mg if needed. Follow-up period was 52 weeks. Results: At 52 weeks in 107 patients aged 65 years and above receiving dual therapy, SBP/DBP decreased significantly (P < 0.001) from baseline by 30 ± 12/14 ± 9 mmHg with indapamide SR/amlodipine (n = 53) vs 22 ± 16/11 ± 9 mmHg with enalapril/amlodipine (n = 54). There was a significantly greater SBP reduction of 6.2 ± 2.7 mmHg (P = 0.022, adjusted on baseline) with indapamide SR/amlodipine vs enalapril/amlodipine, a larger difference than that seen in all ages on bitherapy (4.1 ± 1.5 mmHg; P = 0.006). Moreover, BP response rate (<140/90 mmHg or decrease of 20 mmHg in SBP or 10 mmHg in DBP) in patients aged 65 years and above was greater with indapamide SR/amlodipine (88%) than with enalapril/amlodipine (75%). Indapamide SR and amlodipine were associated with a good safety profile. Three patients in each group discontinued treatment. Figure. No caption available. Conclusions: This analysis indicates that a thiazide-like diuretic/CCB combination (indapamide SR/amlodipine) more effectively lowers SBP than an angiotensin-converting enzyme inhibitor/CCB combination in these hypertensive patients aged 65 years and above, whilst maintaining a good safety profile.